The ADHD toolkit - Wheeler, Linda (Los Angeles : Sage Publications, 2010)
Are you struggling with students who have ADHD (Attention-Deficit Hyperactivity Disorder)? There is likely to be at least one student in any mainstream class with ADHD, an evolving concept that affects pupils' learning, concentration, behaviour and social relationships. In order to offer effective support and maximize the learning potential of all students in your classroom you will need to understand the different needs of all children, but perhaps especially those with ADHD. With sections covering the background to ADHD, the school setting and the wider context of home life, this complete re.
Includes index.
Keywords: Attention-deficit-disordered children -- Education; Attention-deficit hyperactivity disorder